Physiological overview of Human Ageing process - Joel Simon, Christopher; Gayathri; Duraisawamy, Revathy; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
The impact that aging has on organisms is a complex interaction between the processes of aging at a cellular, organ, and integrated systems level and the effects of environmental factors such as nutrition, infection, and trauma. Physiologic aging involves changes that tend to be linear with time and are characteristically decremental in nature. A number of the functional changes can be delayed in onset or slowed in their progress by lifestyle. Aging challenges the reserves of function that allow for activity above the resting level and for regulation of the internal environment. Physiological changes occur with aging in all organ systems. The cardiac output decreases, blood pressure increases, and arteriosclerosis develops. The lungs show impaired gas exchange, a decrease in vital capacity, and slower expiratory flow rates. The creatinine clearance decreases with age, although the serum creatinine level remains relatively constant due to a proportionate age-related decrease in creatinine production. Functional changes, largely related to altered motility patterns, occur in the gastrointestinal system with senescence, and atrophic gastritis and altered hepatic drug metabolism are common in the elderly. Progressive elevation of blood glucose occurs with age on a multifactorial basis, and osteoporosis is frequently seen due to a linear decline in bone mass after the fourth decade. The epidermis of the skin atrophies with age, and due to changes in collagen and elastin, the skin loses its tone and elasticity. Lean body mass declines with age, and this is primarily due to loss and atrophy of muscle cells. Degenerative changes occur in many joints, and this, combined with the loss of muscle mass, inhibits elderly patients' locomotion. These changes with age have important practical implications for the clinical management of elderly patients.